2018
DOI: 10.4103/abr.abr_135_18
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Markers SOX-2 and OCT-4 Enable to Resolve the Diagnostic Dilemma between Ameloblastic Carcinoma and Aggressive Solid Multicystic Ameloblastoma

Abstract: Background:Ameloblastic carcinoma (ACA) is a malignant neoplasm with overlapping histopathological features of benign aggressive solid multicystic ameloblastoma (SMA). This often leads to misdiagnosis with direct implication on the management protocol. The need of the hour is to adopt reliable tissue biomarkers to differentiate these lesions accurately that will help to implement an appropriate treatment modality. Few studies to differentiate ACA and SMA in literature with a limitation of a single marker and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 28 publications
1
35
1
Order By: Relevance
“…Octamer-binding protein 4 is a homeodomain transcription factor belonging to the Pit-Oct-Unc family. 58 It has been well established to be one of the most crucial transcription factors that aid in controlling the self-renewal and pluripotency of embryonic stem cells. 59 The OCT4 expression has also been considered as one of the nonsurface markers of CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Octamer-binding protein 4 is a homeodomain transcription factor belonging to the Pit-Oct-Unc family. 58 It has been well established to be one of the most crucial transcription factors that aid in controlling the self-renewal and pluripotency of embryonic stem cells. 59 The OCT4 expression has also been considered as one of the nonsurface markers of CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of SOX2 has been investigated in the epithelial component of a number of odontogenic lesions. AMB was found negative for SOX2, 13‐17 but ameloblastic carcinoma 13,16,17 and recurrent AMB 13 were SOX2+, probably reflecting their biological behavior. In contrast, others reported expression of SOX2 in AMB 18,19 and suggested that since SOX2 expression was also positive in dental lamina of developing human primary molars and third molars, it probably acts in maintaining the progenitor state of ameloblastic epithelium and that AMB may originate from SOX2‐expressing dental lamina epithelium 18 .…”
Section: Discussionmentioning
confidence: 94%
“…The expression of Oct4, known to play a critical role in the development and self‐renewal of embryonal stem cells and in the invasiveness and chemoresistance of certain cancers, 38 has been found to be negative in the present study. Previous works, in which Oct4 has been examined in the epithelial component of odontogenic lesions, reported equivocal expression, ranging from negative in AMB, DC, and OKC, 14,15 through scarcely positive in radicular cysts 14 and to definitely positive in AMB and OKC, 16,39 and in AOT and ameloblastic carcinoma 14 . In other types of tumors, it has been shown that stem cell markers, such as Nanog and SOX2, were differentially expressed in the epithelial and stromal components 4 and that the relative frequency of these cells was tissue‐related 40 .…”
Section: Discussionmentioning
confidence: 95%
“…Expression were categorized into 1 of 3 groups: (0) Negative = 0 point, (1) Low = 1-3 points, and (2) High = 4-7 points. [20] GPC3 expression was considered positive when brown cytoplasmic staining of the tumor cells was detected. Expression percentages were graded from 0 to 4 according to the following levels: 0%, 1%-25%, 26%-50%, 51%-75% and 76%-100%.…”
Section: Discussionmentioning
confidence: 99%